High Dose Frusemide in Established Acute Renal Failure. Issue 5890 (24th November 1973) - Cantarovich, F.; Galli, C.; Benedetti, L.; Chena, C.; Castro, L.; Correa, C.; Loredo, J. Perez; Fernandez, J. C.; Locatelli, A.; Tizado, J.
Abstract : The results of treatment with frusemide in 105 patients with established acute renal failure admitted during the past six years were reviewed and compared with control groups. Daily doses of 2, 000 mg of frusemide administered from the day of admission onwards produced a significant increase in the number of patients who attained a diuresis and decreased the duration of oliguria. The reduction in the time spent in hospital and in the number of dialyses required suggests that the use of frusemide in these large doses is indicated in patients with severe established acute renal failure.